PENERAPAN ARTIFICIAL INTELLIGENCE DALAM MENUNJANG PEMAHAMAN MATEMATIKA SISWA SEKOLAH DASAR - Srianti; Adrias Adrias; Aissy Putri Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics education at the elementary school level has a big challenge in improving students' conceptual understanding and skills. With the rapid development of technology, the use of artificial intelligence (AI) has attracted attention as a solution to overcome problems in learning. The purpose of this study was to determine how the application of artificial intelligence (AI) supports elementary school students' mathematical understanding, and to determine the impact of the application of artificial intelligence (AI) in supporting elementary school students' understanding of mathematics. By using a qualitative approach with a descriptive method to understand the application of artificial intelligence (AI) in supporting elementary school students' understanding of mathematics. The results of this study indicate that the use of artificial intelligence (AI) when learning mathematics at SDN 28 Koto Merapak has been shown to have a significant impact on students' conceptual understanding, especially in Grade VI. In addition, AI technology can increase students' motivation and commitment to learning.